Exceptional Electromagnetic Interference Shielding Using Single-Walled Carbon Nanotube/Conductive Polymer Composites Films with Ultrathin, Lightweight Properties - Nguyen, Thi Thuy Linh; Cho, Soo Jin; Ko, Jaehyoung; Nguyen, Dinh Cung Tien; Kim, Min Woo; Kim, Nam Dong; Lee, Dong Su; Joo, Yongho (Pergamon Press Ltd., 2024)
The fundamental integrity of electronic devices depends heavily on appropriate electromagnetic protection measures. In this work, thin films of single-walled carbon nanotubes (SWCNTs) and poly(3,4-ethylene dioxythiophene): poly(styrene sulfonate) composites are presented, and their electromagnetic interference shielding effectiveness (EMI SE) is assessed in the X-band frequency range. The films are prepared via a simple benchtop process involving a vacuum filtration followed by a dip-coating. Notably, the composite with the highest thickness, measuring 2.12 μm, achieved the highest EMI SE of 55.53 dB, whereas the thinnest, measuring 0.24 μm, exhibited the highest specific SE divided by thickness (SSE/t) of 2,230,000 dB cm2 g？1. Additionally, the composites demonstrated excellent physical and chemical stability, maintaining their performance under various harsh conditions. The highest shielding performance of our composite films among reported carbon-based polymer materials is attributed to the complementary spatial arrangement of inherently conducting materials, namely, the SWCNT and the conducting polymer. Our contribution here lays the groundwork for creating lightweight, flexible composites with superior EMI shielding performance, targeting next-generation flexible electronics.